A111 Transport and Child Well-Being. Issue 2 (June 2015) - Waygood, Edward; Friman, Margareta; Olsson, Lars; Taniguichi, Ayako
Abstract: Background: Reviews on children's travel have previously examined topics such as active travel to school, independent travel, physical activity, and crashes. If research on children's travel has the ultimate goal of improving children's well-being, there is no general synthesis on the research linking it with transportation. This review takes a broad look at interactions between transport and child well-being. It organizes the findings into the five main domains of child well-being: physical, psychological, cognitive, social, and economic. Methods: A review was conducted that sought articles related to the topic of transport/mobility and child(ren). The main search engine used was Web of Science, with additional searches carried out in medial, sociology, and anthropology search engines. After eliminating papers related to topics covered in previous reviews, a total of 102 relevant papers were reviewed. Results: The review found that apart from the physical domain (related to previous reviews), the relationship between transportation and the other domains of child well-being is not yet well developed, though more papers were found for psychological and social well-being, and very few for economic well-being. For each domain, a table summarises the positive and negative relationships. Walking had ten positive findings and two negative. Cycling had seven positive and two negative. Active transport had two positive. Bus travel (city, not school) had two positive and one negative (generally understudied mode for children's travel). Train travel had two positive. Independent mobility had fourteen positive associations. School buses had one negative finding. Car travel had two positive and five negative findings. Passive travel had one negative finding. General transport (typically traffic) had one positive and seventeen negative. Thus, it would appear that independent mobility is either better studied, or is more associated with positive findings (as inconclusive or contrasting findings were not included in the tables). In very few cases were similar studies found, so that it is difficult to know how robust the findings are. Conclusions: Many studies are conducted to explain children's travel, but research relating child well-being to transport is still underdeveloped, apart perhaps related to physical well-being. Very few papers were found that directly related to economic well-being of children.